2001
DOI: 10.3758/bf03194916
|View full text |Cite
|
Sign up to set email alerts
|

Fluency of retrieval at study affects judgments of learning (JOLs): An analytic or nonanalytic basis for JOLs?

Abstract: The fluency of retrieval during a test of memory has been implicated as a cue for judgments of learning (JOLs), but little is known about how fluency affects JOLs. In three experiments, we investigated (1) whether the fluency of generation during study may be a cue for JOLs and (2) whether such fluency effects are mediated by an analytic or nonanalytic inference. To accomplish our goals, we used a learner-observer-judge method. While studying paired associates, learners generated some targets at study. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
113
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 23 publications
12
113
2
Order By: Relevance
“…The direction of causality has been described as going from subjective judgments to behaviors (e.g., Koriat & Goldsmith, 1996;Nelson & Narens, 1990;Son & Schwartz, 2002), and from behaviors to subjective judgments (Benjamin & Bjork, 1996;Hertzog, Dunlosky, Robinson, & Kidder, 2003;Kelley & Jacoby, 1996;Matvey, Dunlosky, & Guttentag, 2001).…”
Section: The Relationship Between Monitoring and Control And Its Effementioning
confidence: 99%
“…The direction of causality has been described as going from subjective judgments to behaviors (e.g., Koriat & Goldsmith, 1996;Nelson & Narens, 1990;Son & Schwartz, 2002), and from behaviors to subjective judgments (Benjamin & Bjork, 1996;Hertzog, Dunlosky, Robinson, & Kidder, 2003;Kelley & Jacoby, 1996;Matvey, Dunlosky, & Guttentag, 2001).…”
Section: The Relationship Between Monitoring and Control And Its Effementioning
confidence: 99%
“…We suggest that this occurred because participants regarded large items as subjectively more fluent and, thus, more memorable than small items. Other work has shown that predictions of future performance can be sensitive to fluency (Begg et al 1989;Benjamin et al, 1998;Hertzog et al, 2003;Koriat & Ma'ayan, 2005;Matvey et al, 2001; see also Kelley & Lindsay, 1993). For example, Begg et al (1989) suggested that participants "predict success for items that are easiest to process in the manner demanded by the task" (p. 610).…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have demonstrated that enhancing the familiarity of a cue, for example, through repetition (e.g., Metcalfe, Schwartz, & Joaquim, 1993; see also Jameson, Narens, Goldfarb, & Nelson, 1990), elevates levels of prospective confidence. In addition, there is some indication that both ease of encoding (Begg et al, 1989;Hertzog, Dunlosky, Robinson, & Kidder, 2003) and the ease with which an item is retrieved before a JOL is made (e.g., Benjamin et al, 1998;Matvey, Dunlosky, & Guttentag, 2001) influence such judgments, so that participants regard easily retrieved or processed items as having a high probability of later recall. However, the prior evidence is at best indirect, and an understanding of the potential influence of perceptual qualities of stimuli on predictions of memory performance requires a direct manipulation of such qualities.…”
mentioning
confidence: 99%
“…Although possible, previous research suggests that people do not have direct access to states of items in memory but that, instead, their judgments are based on heuristics and influenced by any number of cues (Serra & Metcalfe, 2009). These cues include item relatedness (Carroll, Nelson, & Kirwan, 1997;Koriat, 1997;Rabinowitz, Ackerman, Craik & Hinchley, 1982) and processing fluency (Koriat & Ma'ayan, 2005;Matvey, Dunlosky, & Guttentag, 2001), which in themselves can be predictive of subsequent performance.…”
mentioning
confidence: 99%